Anisotropic tomography around La Réunion Island from Rayleigh waves - Mazzullo, A; Stutzmann, E; Montagner, J; Kiselev, S; Maurya, S; Barruol, G; Sigloch, K (Wiley, 2017)
In the western Indian Ocean, the Réunion hot spot is one of the most active volcanoes on Earth. Temporal interactions between ridges and plumes have shaped the structure of the zone. This study investigates the mantle structure using data from the Réunion Hotspot and Upper Mantle-Réunions Unterer Mantel (RHUM-RUM) project, which significantly increased the seismic coverage of the western part of the Indian Ocean. For more than 1 year, 57 ocean bottom seismometer stations and 23 temporary land stations were deployed over this area. For each earthquake station path, the Rayleigh wave fundamental mode phase velocities were measured for the periods from 30 s to 300 s and group velocities for the period from 16 s to 250 s. A three-dimensional model of the shear velocity in the upper mantle was built in two steps. First, the path mean phase and group velocities were inverted, to obtain regionalized velocity maps for each separate period. Then, all of the phase and group velocity maps were combined and inverted at each grid point, to obtain the local S wave velocity as a function of depth, using a transdimensional inversion scheme. The three-dimensional anisotropic S wave velocity model has resolution down to 300 km in depth. The tomographic model and surface tectonics are correlated down to ∼100 km in depth. Starting at 50 km in depth, a slow velocity anomaly beneath Rodrigues Ridge and the east-west orientation of the azimuthal anisotropy show a connection between Réunion upwelling and the Central Indian Ridge. The slow velocity signature beneath La Réunion is connected at greater depths (150-300 km) with a large slow velocity zone beneath the entire Mascarene Basin. This develops along a northeast direction, following the general motion direction of the African Plate. These observations indicate nonisotropic spreading of hot plume material and dominant horizontal flow in the upper mantle beneath this area.